Income distribution and the contractionary effect of protection: A theoretical analysis - Sugata Marjit; Tarun Kabiraj (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1992)
In terms of a simple model we show that removal of tariff from a competing foreign brand is likely to expand the size of the domestic industry when income disparities exist. A tariff increases profits of the local monopolist but is capable of cutting down the size of the local industry. After providing the general theoretical condition, we construct an example (from a class of examples) where such an outcome holds in equilibrium.
Keywords: 330